2006
DOI: 10.1038/ni1327
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin expression is essential for interferon-α production by plasmacytoid dendritic cells

Abstract: The observation that the T-bet transcription factor allows tissue-specific upregulation of intracellular osteopontin (Opn-i) in plasmacytoid dendritic cells (pDCs) suggests that Opn might contribute to the expression of interferon-α (IFN-α) in those cells. Here we show that Opn deficiency substantially reduced Toll-like receptor 9 (TLR9)-dependent IFN-α responses but spared expression of transcription factor NF-κB-dependent proinflammatory cytokines. Shortly after TLR9 engagement, colocalization of Opn-i and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
351
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(361 citation statements)
references
References 62 publications
3
351
0
7
Order By: Relevance
“…The OPN-siRNA was introduced into the animal with a hydrostatic pressure-mediated technique, hydrodynamic delivery (Liu et al 1999). OPN is thought to function not only in soluble form (OPN-s) as a cytokine but also in intracellular form, OPN-i (Shinohara et al 2006;Cantor and Shinohara 2009). Although anti-OPN Ab can only be accessible to and block OPN-s, OPN-siRNA may block both forms by reducing the expression in both compartments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The OPN-siRNA was introduced into the animal with a hydrostatic pressure-mediated technique, hydrodynamic delivery (Liu et al 1999). OPN is thought to function not only in soluble form (OPN-s) as a cytokine but also in intracellular form, OPN-i (Shinohara et al 2006;Cantor and Shinohara 2009). Although anti-OPN Ab can only be accessible to and block OPN-s, OPN-siRNA may block both forms by reducing the expression in both compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the specific form of OPN, intracellular OPN, could induce IFN- secretion from plasmacytoid dendritic cells (pDC) in the presence of CpG in TLR9-MyD88-and IRF7-dependent manner (Shinohara et al 2006). IFN- also favors Th1-deviation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings have revealed that iOPN also mediates IFN-α expression in plasmacytoid dendritic cells by selectively coupling TLR9 signaling to expression of IFN-α (Shinohara et al, 2006).This indicates that intracellular and secreted OPN may differentially regulate signaling pathways in different cell lineage to influence the type and intensity of immune responses.…”
Section: Intracellular Opnmentioning
confidence: 99%
“…M. Shinohara and H. Cantor (Dana Farber Cancer Institute, Boston, MA) (16). The breeding pairs were homozygous OPN Ϫ/Ϫ mice with 15 generations of backcrossing to the BALB/c background therefore considered 99.99% pure BALB/c background.…”
Section: Animalsmentioning
confidence: 99%